Thermally diffused expanded-core fibers with gain or loss - Kliros, George S (Photonics Letters of Poland, 2009)
We investigate the modal properties of thermally diffused expanded-core fibers (TEC) with loss or gain. The corresponding Helmholtz equation with complex refractive index profile is solved numerically using Galerkin’s method. The imaginary part of the modal electric field results in wave-front distortion showing that the power flows out or into the doped region according to the sign of the imaginary part of the refractive index. The spectral characteristics of the calculated gain or loss are discussed. Our results may potentially be useful to design high power fiber lasers or amplifiers using TEC technique. Full Text: PDF References: K. Shiraishi, Y. Aizawa and S. Kawakami,"Beam expanding fiber using thermal diffusion of the dopant", J. Lightwave Technol. 8, 1151 (1990).[CrossRef] T. Haibara, T. Nakashima, M. Matsumoto, H. Hanafusa, "Connection loss reduction by thermally-diffused expanded core fiber", IEEE Photonics Techn. Lett. 3(4), 348 (1991).[CrossRef] M. Kihara, M. Matsumoto, T. Haibara, S. Tomita, "Characteristics of thermally expanded core fiber", J. Lightwave Techn. 14(10), 2209 (1996). [CrossRef] G. S. Kliros, P. C. Divari, "Coupling characteristics of laser diodes to high numerical aperture thermally expanded core fibers", J. Mater. Sci: Mater. Electron. 20, S59-S62 (2009).[CrossRef] P. C. Divari, G. S. Kliros, "Modal and coupling characteristics of low-order modes in thermally diffused expanded core fibers", Optik 120, 222 (2009).[CrossRef] K. Kima, K. Leea, E. Shina, H. Songa, K. Honga, S. Hwangboa, K. Sohnb, "Characteristics of side-polished thermally expanded core fiber and its application as a band-edge filter with a high cut-off property", Opt. Comm. 180, 51 (2006).[CrossRef] L. V. Nguyen, D. Hwang, D. S. Moon, Y. Chung, "Tunable comb-filter using thermally expanded core fiber and ytterbium doped fiber and its application to multi-wavelength fiber laser", Optics Comm. 281, 5793 (2008).[CrossRef] G. S. Kliros, N. Tsironikos, "Variational analysis of propagation characteristics in thermally diffused expanded core fibers ", Optik 116, 365 (2005).[CrossRef] A. Liu, "Suppressing stimulated Brillouin scattering in fiber amplifiers using nonuniform fiber and temperature gradient", Opt. Express 15, 977 (2007).[CrossRef] S. Savovic, A. Djordjevich, "Influence of initial dopant distribution in fiber core on refractive index distribution of thermally expanded core fibers", Optical Materials 30, 1427 (2008).[CrossRef] G. S. Kliros, P. C. Divari, Proc. of 14th Micro-optics Conf. MOC’08, Brussels, Belgium, p. 135. B. T. Smith, J. M. Boyle, J. J. Dongarra, B. S. Garbow, Y. Ikebe, V. C. Klema and C. B. Moler, Matrix Eigensystem Routines-EISPACK Guide, Lecture Notes in Computer Science 6, ed. G. Goos and J. Hartmanis (Springer, Berlin, 1976).